A comparison of cortico-cortical communication during air-pistol shooting in elite disabled and non-disabled shooters - Kim, W.; Lee, G.; Kim, J.; Woo, M. (Personality and Individual Differences, 2013)
This study examined the difference in electroencephalographic (EEG) coherence, an index of cortico-cortical communication, during air pistol shooting between disabled and non-disabled elite shooters. Participants included 22 non-disabled and 12 disabled members of the Korean national air-pistol shooting team at the world class level. Electrocortical activation was recorded during 20 self-paced 10-meter air pistol shots. Higher cortico-cortical communication between brain regions was observed in disabled shooters. The higher functional communication appears to be a strategy to compensate for the attenuated function of the brain resulting from spinal cord injury. This compensatory mechanism could explain why there is no significant difference in shooting performance between elite disabled and non-disabled shooters.